Peran Sekolah Alam dalam Mewujudkan Pendidikan Inklusif Berbasis Nilai Multikultural: Studi Kasus di Islamic Orbit School Aceh Besar - Ummu Kholifatul Khasanah; Fatia Nurahmi; Siti Mayang Sari; Musdiani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Inclusive education grounded in multicultural values plays a crucial role in providing equitable, child-friendly, and diversity-responsive educational services. This study seeks to examine the role of nature-based schools in implementing inclusive education founded on multicultural values at Islamic Orbit School (iOS) Aceh Besar. A qualitative approach with a case study design was employed in this research. The participants involved the school principal, teachers, inclusion facilitators, and students. Data were collected through classroom observations, in-depth interviews, and document analysis. Data analysis followed the stages of data reduction, data organization, and conclusion drawing, while the trustworthiness of the data was ensured through source and methodological triangulation. The findings indicate that Islamic Orbit School plays a significant role in fostering inclusive education through the implementation of a curriculum based on the Qur’an and children’s innate potential (fitrah), the development of a child-friendly school environment, and the use of nature-based learning as an instructional approach. Multicultural values cultivated in the learning process include respect for diversity, tolerance, empathy, and collaboration among students, including those with special educational needs. This study concludes that nature-based schools have strong potential to serve as a contextual and meaningful model for integrating inclusive education with multicultural values.